Automatizing ontology population to drive the navigation on Virtual Learning Spaces - Araújo, Cristiana (2017)
The creation of Learning Spaces on the Web, like the exhibition rooms of virtual museums, supported by an ontology that enables a conceptual navigation over the learning objects exposed, is an hard and complex task but of uttermost importance for the success of the knowledge acquisition process. In our opinion, the creation must be systematic and reusable from case to case, based on the query of the ontology instances that describe the museum assets. We will discuss how the ontology definition drives the way SPARQL (SPARQL Protocol and RDF Query Language) queries extract information from the TripleStore to be prepared for visualization. However, to enable this approach, we need to populate the ontology in an automatic way, extracting the data from the annotated documents in the institution repository. We intend to show how that process can be implemented using the Museum of the Person (MP) as a case-study, describing the XML2RDF tool developed. To illustrate the complete approach proposed we will include a guided visit to the exhibition rooms of MP created according to that proposal and by our tools.